Stone provenance and conservation of the Trinitarias Descalzas of San Ildefonso convent, Madrid (Spain) - Freire-Lista, David Martín; Fort González, Rafael (Ge-conservacion, 2017)
The characterization of building stones used in monuments and the location of their historic quarries is key for maintenance and restoration works. The four most representative building stones of Madrid: flint, granite, Cretaceous dolostone and Miocene limestone, have been used in the Trinitarias Descalzas of San Ildefonso convent of this city. A plaque of Carrara marble was placed on the convent façade in honour of the Spanish writer Miguel de Cervantes in 1870. The decay of the stones was determined by characterization techniques such as optical polarization and fluorescence microscopy and spectrophotometry. This technique gave information about the colour change between the plinth granite of the convent and quarry granite where it was extracted. The historical documentation complements these data.